2019
DOI: 10.1186/s13756-019-0651-y
|View full text |Cite
|
Sign up to set email alerts
|

Bombyx mori gloverin A2 alleviates enterotoxigenic Escherichia coli-induced inflammation and intestinal mucosa disruption

Abstract: Background: Enterotoxigenic Escherichia coli (ETEC) is one of the leading bacterial causes of intestinal inflammation and diarrhea. However, the ETEC is frequently resistant to common antibiotics. In this study, we explored the role of a novel antibacterial peptide Bombyx mori gloverin A2 (BMGlvA2) in alleviating ETEC-induced inflammation and intestinal epithelium disruption in mice. Methods: An ETEC-challenged mice model was used, and the ETEC-challenged mice and non-challenged mice were treated by the BMGlvA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…ETEC has been demonstrated to induce cell death and decrease the expression of tight junction proteins in intestinal epithelial cells ( 29 31 ) and a mouse model ( 32 ). In this experiment, we also found that ETEC significantly decreased the expression of tight junction proteins.…”
Section: Discussionmentioning
confidence: 99%
“…ETEC has been demonstrated to induce cell death and decrease the expression of tight junction proteins in intestinal epithelial cells ( 29 31 ) and a mouse model ( 32 ). In this experiment, we also found that ETEC significantly decreased the expression of tight junction proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The TJ structure is composed of TJ proteins, such as ZO-1, occludin, and claudins, which are an important part of the intestinal epithelial barrier and play important roles in intestinal epithelial cells ( Huang et al, 2020 ). Lin et al (2019) investigated the effect of the antimicrobial peptide gloverin A2 (BMGlvA2) on ETEC-induced intestinal barrier disruption in mice and found that it clearly improved the expression of the TJ protein ZO-1 in the intestine after ETEC infection. Zhang et al (2019) found that the hybrid peptide LL-37-Tα1 (LTA) could increase the LPS-induced expression of ZO-1 and occludin in the jejunum of mice, thereby improving intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…ETEC has been demonstrated to induce cell death and decrease the expression of tight junction proteins in intestinal epithelial cells (29)(30)(31)) and a mouse model (32). In this experiment, we also found that ETEC significantly decreased the expression of tight junction proteins.…”
Section: Discussionsupporting
confidence: 69%